Exploring student perspectives on AI-generated feedback using a Socratic method chatbot - Nahar, Nurun (Journal of Learning Development in Higher Education, 2025)
The integration of Artificial Intelligence (AI) in educational settings has opened new avenues for enhancing student learning. This study investigated the use of a generative AI chatbot, trained to provide feedback using the Socratic Method, in a Business Management programme. Recent literature highlights the transformative potential of AI in education, particularly in fostering personalised learning experiences and supporting critical thinking (Gökçearslan et al., 2024; Lee and Moore, 2024; Mustafa et al., 2024). Understanding student perspectives on AI-generated feedback is crucial for optimising its use in learning development. This study aimed to evaluate the effectiveness of AI feedback in promoting critical thinking and its acceptance among students. Previous research has shown that AI chatbots can enhance learning by providing timely and relevant feedback, though challenges such as limited interaction and potential for misleading guidance remain (Banihashem et al., 2024; Gökçearslan et al., 2024; Guo et al., 2024). A qualitative approach was employed, utilising a focus group with n=14 final-year undergraduate students on a Business Management pathway. The generative AI tool was piloted to provide feedback on student drafts for summative coursework. The quality of feedback was assessed based on its accuracy, relevance, timeliness, and effectiveness in fostering critical thinking. Data was analysed using thematic analysis, a method well-suited for identifying and interpreting patterns within qualitative data (Nowell et al., 2017; Braun and Clarke, 2022). The Socratic Method, known for its effectiveness in promoting critical thinking through questioning, was employed as the feedback mechanism (Buckingham Shum, 2024). The study revealed that students found AI-generated feedback useful and relevant for improving their work and identifying knowledge gaps, thereby promoting deep learning. The Socratic Method used by the AI encouraged deeper engagement with their work, unlike the straightforward answers typically provided by other chatbots. However, students preferred tutor feedback.